Leichenschau: Wahrnehmungen, Erfahrungen und Compliance von Krankenhausärzten im ländlichen Raum - Schwarz, Clara-Sophie; Müller-Schwarz, M.; Yen, Kathrin; Germerott, Tanja (Rechtsmedizin, 2019)
BackgroundThe practice of performing a post-mortem external examination of a corpse has been repeatedly criticized in Germany during the last decades. Various experts asked for improvements to make the results of post-mortem external examinations more reliable. Preparing strategies for improvement requires detailed knowledge of the established processes outside the specialist field of forensic medicine.ObjectiveThe aim of this study was to ask for impressions, experiences and compliance of hospital physicians in rural areas in terms of postmortem external examination of a corpse and to illustrate them in the context of the required quality enhancement.Material and methodsMedical practitioners (internal medicine, surgery, anesthesiology) in hospitals in a selected rural area were asked to fill out an online questionnaire. The extracted data were analyzed and diagrammed.Results and discussionMore than one third of the respondents did not correctly name the requirements of a post-mortem external examination of a corpse. The survey results emphasize the importance of retraining.ConclusionA factor that can be influenced seems to be motivation; it is crucial that postmortem external examinations of a corpse are accepted as a responsible and important everyday task for physicians.